Rotational Symmetry of Two Pyrethroid Receptor Sites in the Mosquito Sodium Channel - Du, Yuzhe (Mol Pharmacol, 2015)
Voltage-gated sodium channels are the primary target of pyrethroid insecticides. Although it is well known that specific mutations in insect sodium channels confer knockdown resistance (kdr) to pyrethroids, the atomic mechanisms of pyrethroid-sodium channel interactions are not clearly understood. Previously, computer modeling and mutational analysis predicted two pyrethroid receptors, pyrethroid receptor site 1 (PyR1) (initial) and pyrethroid receptor site 2 (PyR2), located in the domain interfaces II/III and I/II, respectively. The models differ in ligand orientation and the number of transmembrane helices involved. In this study, we elaborated a revised PyR1 model of the mosquito sodium channel. Computational docking in the K(v)1.2-based open channel model yielded a complex in which a pyrethroid (deltamethrin) binds between the linker helix IIL45 and transmembrane helices IIS5, IIS6, and IIIS6 with its dibromoethenyl and diphenylether moieties oriented in the intra- and extracellular directions, respectively. The PyR2 and revised PyR1 models explained recently discovered kdr mutations and predicted new deltamethrin-channel contacts. Further model-driven mutagenesis identified seven new pyrethroid-sensing residues, three in the revised PyR1 and four in PyR2. Our data support the following conclusions: 1) each pyrethroid receptor is formed by a linker-helix L45 and three transmembrane helices (S5 and two S6s); 2) IIS6 contains four residues that contribute to PyR1 and another four to PyR2; 3) seven pairs of pyrethroid-sensing residues are located in symmetric positions within PyR1 and PyR2; and 4) pyrethroids bind to PyR1 and PyR2 in similar orientations, penetrating deeply into the respective domain interfaces. Our study elaborates the dual pyrethroid-receptor sites concept and provides a structural background for rational development of new insecticides.